Students’ Difficulties in Mastering Structure and Written Expression Of Paper-Based TOEFL - Muhajir Muhajir (Universitas Syiah Kuala, 2018)
Obtaining a score of TOEFL higher than 500 has been proven difficult. Some studies showed that students had biggest problems in answering section two of PBT TOEFL. Therefore, this study was aimed at investigating difficulties encountered by advanced EFL learners in mastering structure and written expression tested in PBT TOEFL. The PBT TOEFL test, designed by ETS, was conducted to 25 advanced undergraduate students, selected by using a convenient sampling technique, at Syiah Kuala University. The test consisted of 40 multiple choice questions and the students completed it within 25 minutes. The result revealed that the students faced a serious problems with redundancy (48%), followed by verb form (53%), pronoun error (55%), plural (55%), WIAS (57%), parallelism (59%), article (60%), word order (61%), conjunction (62%), deleted word (71%), prepositional phrase (71%), word choice (73%), and part of speech (74%). It was concluded that redundancy was the most difficult aspect for the students. Hence, it is suggested that university lectures who teach structure pay more attention to this aspect.